2012
DOI: 10.1111/j.1747-4949.2012.00797.x
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Based Therapy for Experimental Stroke: A Systematic Review and Meta-Analysis

Abstract: Stem cell therapy holds great promise in medicine, but clinical development should be based on a sound understanding of potential weaknesses in supporting experimental data. The aim of this article was to provide a systematic overview of evidence relating to the efficacy of stem cell-based therapies in animal models of stroke to foster the clinical application of stem cell-based therapies and to inform the design of large-scale clinical trials. We conducted a systematic search for reports of experiments using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
124
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 13 publications
(15 reference statements)
1
124
1
Order By: Relevance
“…This includes many different types of stem cell therapeutic candidates. 4,5 Mesenchymal stromal cells (MSCs) (also known as marrow stromal cells and marrow stem cells) are a form of multipotent adult stem cells that have received considerable attention, in part because of their relative ease of isolation from tissues such as bone marrow and their immunoprivileged status. The International Society for Cellular Therapy defines MSCs on the basis of adhering to plastic in standard culture conditions, expressing characteristic surface antigens (e.g., CD105 and CD90, but not CD45 or HLA-DR), and having the ability to differentiate in vitro to osteoblasts, adipocytes, and chondroblasts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This includes many different types of stem cell therapeutic candidates. 4,5 Mesenchymal stromal cells (MSCs) (also known as marrow stromal cells and marrow stem cells) are a form of multipotent adult stem cells that have received considerable attention, in part because of their relative ease of isolation from tissues such as bone marrow and their immunoprivileged status. The International Society for Cellular Therapy defines MSCs on the basis of adhering to plastic in standard culture conditions, expressing characteristic surface antigens (e.g., CD105 and CD90, but not CD45 or HLA-DR), and having the ability to differentiate in vitro to osteoblasts, adipocytes, and chondroblasts.…”
mentioning
confidence: 99%
“…The current review, by focusing on one specific cellular therapy for one specific clinical indication, builds on prior meta-analyses that took a broader approach to stem cell therapy. 4,5,15 First, in accordance with recent Stroke Therapy Academic Industry Roundtable (STAIR) recommendations 16 and a recent NIH workshop, 17 the quality of the studies was reviewed. Second, the effect size of MSCs was determined for the most frequently used behavioral and histologic outcomes.…”
mentioning
confidence: 99%
“…MSCs have been shown to exert profound immunomodulatory properties and have gained approval as a treatment in certain countries for graft versus host disease. Several meta-analyses have consistently demonstrated their treatment effects in various animal models of stroke [19][20][21][22][23][24]. In fact, MSCs are likely the most widely studied type of cell therapy in the preclinical stroke literature [1][2][3].…”
Section: Bone Marrow Stromal Cellsmentioning
confidence: 99%
“…[17][18][19] There is resulting reduction in infarct volume and functional recovery has generally been enhanced. Publication and reporting bias is evident in the animal literature, study quality has been inconsistent, and effect sizes may be overestimated as a result, 17,19 although meta-analysis of studies of mesenchymal stem cells (MSCs) in rodent stroke suggested larger effect sizes with greater study quality.…”
Section: The Acute or Early Subacute Paradigmmentioning
confidence: 99%
“…[17][18][19] There is resulting reduction in infarct volume and functional recovery has generally been enhanced. Publication and reporting bias is evident in the animal literature, study quality has been inconsistent, and effect sizes may be overestimated as a result, 17,19 although meta-analysis of studies of mesenchymal stem cells (MSCs) in rodent stroke suggested larger effect sizes with greater study quality. 18 There is no compelling evidence favouring one type of cell over another, 20 with a wide range of (predominantly human) cell types having similar effects in rodent focal ischaemia models, including MSCs, mixed bone marrow mononuclear cell (BMMCs), CD34+ haematopoietic progenitor cells, umbilical cord blood cells and many others.…”
Section: The Acute or Early Subacute Paradigmmentioning
confidence: 99%